(untitled) (Proceedings of International Educators Conference, 2024)
This article examines the scientific and theoretical issues of taxation of enterprises in the service sector in Uzbekistan, the development of the service sector based on individual approaches, providing business entities with financial resources and infrastructure, as well as the introduction of a favorable tax regime in Uzbekistan.it requires research work. At the same time, it highlights the entry into a new level of service for business entities, further improving the literacy of the population in the field of tax administration, improving administration based on business support, creating equal conditions for competition and guaranteeing consumer rights, as well as encouraging active participation of the general public in curbing the hidden economy. At the same time, industries are being studied, foreign experience is being formed, scientific and practical conclusions and proposals for its application in our country.